Analisis Hubungan Penggunaan Air Bersih dan Jamban Keluarga dengan Kejadian Diare Pada Balita - Hamzah B; Sudirman (Universitas Widya Gama Mahakam Samarinda, 2021)
Background: Diarrhea is still a health problem in the world, there are about 2 million cases of diarrhea worldwide every year, and 1,9 million children under five die from diarrhea every year. Diarrheal disease in Indonesia is an endemic disease and has the potential for extraordinary events. Diarrhea is the 3 highest infectious disease in North Sulawesi in 2016 with a total of 23.881 cases. Objectives: His study aims to analyze the relationship between the use of clean water and the use of latrines with the incidence of diarrhea in children under five in Gogagoman Village, Kotamobagu in 2020. Research methods: This type of research is observational analytic with cross sectional design with a total sample of 43 respondents. The sampling technique used is accidental sampling. Data were collected by direct interviews with respondents and analyzed univariately and bivariately using the chi square test. Results: The results showed that 44,6% of respondents who had children under five suffered from diarrhea, 40,8% of respondents who used clean water did not meet the requirements, 41,5% of respondents who used latrines did not meet health requirements. The statistical test results showed that there was a relationship between the use of stick water and the incidence of diarrhea in children under five (p=0,023<0,05) and there was a relationship between latrine use and the incidence of diarrhea among children under five (p=0,000<0,05) in Gogagoman Village, Kotamobagu. Conclusion: here is a relationship between the use of clean water and the use of latrines with the incidence of diarrhea in children under five in Gogagoman Village, Kotamobagu in 2020.